Clinical impact of bile‐derived exosomal microRNAs as novel diagnostic and prognostic biomarkers for biliary tract cancers. Issue 1 (17th October 2022) - Yoshida, Michihiro; Yukawa, Hiroshi; Hayashi, Kazuki; Naitoh, Itaru; Miyabe, Katsuyuki; Hori, Yasuki; Natsume, Makoto; Jinno, Naruomi; Kato, Akihisa; Kachi, Kenta; Asano, Go; Sahashi, Hidenori; et al.
Abstract: Sampling of bile juice during endoscopic retrograde cholangiopancreatography (ERCP) has potential benefit of being amenable to the identification of novel biomarkers in liquid biopsy. This study reports the results of a global investigation of exosomal microRNAs (miRNAs) in bile to identify potential biomarkers for biliary tract cancers (BTCs). Eighty‐eight bile samples collected during ERCP (45 BTC and 43 noncancer control samples) were enrolled in this study. Eleven BTC samples and nine control samples were assigned as the discovery set. Exosomes in bile and serum samples were collected using a glass membrane column with size‐controlled macroporous glass (MPG), and exosomal miRNA expression profiles were evaluated using comprehensive miRNA microarray analysis (3D‐Gene). For validation, exosomal miRNA in the bile samples of 34 BTCs and 34 controls were comprehensively evaluated using 3D‐Gene. In the discovery set, eight exosomal miRNAs in bile were identified as significant aberrant expression markers, while no miRNA with aberrant expression in serum was identified. In a comparison of the discovery and validation sets, miR‐451a and miR‐3619‐3p were identified as reproducible upregulated markers, and the combination of the two bile miRNAs showed an excellent area under the curve (0.819) value for diagnosing BTCs. In addition, high miR‐3619‐3p expression in bile reflects poorer prognosis of BTCs (hazard ratio = 2.89). The MPG‐extracted exosomal miRNAs in bile aspirated during ERCP provide a convenient new approach for diagnosing biliary diseases. Bile‐derived miRNA analysis with miR‐451a and miR‐3619‐3p represents a potentially valuable diagnostic strategy for identifying BTCs as well as a predictive indicator of BTC prognosis. Abstract : In a comparison of the discovery and validation sets, miR‐451a and miR‐3619‐3p were identified as reproducible upregulated markers, and the combination of the two bile miRNAs showed an excellent area under the curve (0.819) value for diagnosing BTCs. In addition, high miR‐3619‐3p expression in bile reflects poorer prognosis of BTCs (hazard ratio = 2.89). Bile‐derived miRNA analysis with miR‐451a and miR‐3619‐3p represents a potentially valuable diagnostic strategy for identifying BTCs as well as a predictive indicator of BTC prognosis.